2017
DOI: 10.1016/j.bbmt.2016.12.634
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Monitoring after Autologous Stem Cell Transplantation and Preemptive Rituximab Treatment of Molecular Relapse; Results from the Nordic Mantle Cell Lymphoma Studies (MCL2 and MCL3) with Median Follow-Up of 8.5 Years

Abstract: The main objectives of the present study were to monitor minimal residual disease (MRD) in the bone marrow of patients with mantle cell lymphoma (MCL) to predict clinical relapse and guide preemptive treatment with rituximab. Among the patients enrolled in 2 prospective trials by the Nordic Lymphoma Group, 183 who had completed autologous stem cell transplantation (ASCT) and in whom an MRD marker had been obtained were included in our analysis. Fresh samples of bone marrow were analyzed for MRD by a combined s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 32 publications
(47 reference statements)
0
48
0
Order By: Relevance
“…This study demonstrated that rituximab maintenance can improve survival after SCT. MRD assessment in MCL has not been systematically implemented in clinical practice; however, a few studies have shown the critical clinical significance of MRD‐positive disease status and risk of predicting future relapses . Another issue for MRD assessment in MCL is optimization of the technique according to the tissue type used to test MRD, as not all patients have bone marrow involvement at diagnosis and not all patients have peripheral blood lymphocytosis sufficient enough for testing MRD by either flow cytometry or PCR (allele specific quantitative oligonucleotide polymerase chain reaction).…”
Section: Advances In the Treatment Of MCLmentioning
confidence: 99%
“…This study demonstrated that rituximab maintenance can improve survival after SCT. MRD assessment in MCL has not been systematically implemented in clinical practice; however, a few studies have shown the critical clinical significance of MRD‐positive disease status and risk of predicting future relapses . Another issue for MRD assessment in MCL is optimization of the technique according to the tissue type used to test MRD, as not all patients have bone marrow involvement at diagnosis and not all patients have peripheral blood lymphocytosis sufficient enough for testing MRD by either flow cytometry or PCR (allele specific quantitative oligonucleotide polymerase chain reaction).…”
Section: Advances In the Treatment Of MCLmentioning
confidence: 99%
“…The data suggest that patients, who do not achieve PET negativity or patients with quantifiable MRD in PB after the induction, might benefit from a different (more intensive or innovative) maintenance therapy than rituximab only, eg, obinutuzumab or rituximab plus lenalidomide or other (Figure D, Supplemental Figure 3). In addition, it was demonstrated that a molecular relapse precedes the clinical one, and it could be treated with a preemptive rituximab in the cohort of patients without rituximab maintenance . However, the role of molecular relapse and its management in the cohort of patients on rituximab maintenance remains to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In a number of prospective reports, a pre-emptive rituximab treatment of MRD positive patients was able to reconvert them to MRD negativity, with the possibility of also prolonging their PFS. 8,17 Nevertheless, some limitations still hamper the widespread use of MRD analysis in clinical routine. The two major obstacles as far as methodology is concerned are the need for patient-specific primers and standardization issues.…”
mentioning
confidence: 99%
“…Finally, although the predictive role of MRD has been established in MCL, [3][4][5] evidence for the usefulness of subsequent treatment tailoring based on the MRD results is unfortunately still scarce due to the lack of MRD-driven phase III trials in MCL. 8,17 Moreover, no MRD data are available yet in the context of the new targeted treatments, such as the Bruton's tyrosine kinase inhibitor ibrutinib.…”
mentioning
confidence: 99%
See 1 more Smart Citation